DESAFIOS DA IMPLEMENTAÇÃO E MANUTENÇÃO DA HIGIENE ORAL DE CRIANÇAS DO TRANSTORNO DO ESPECTRO AUTISTA(TEA) (REMUNOM, 2025)
Autism Spectrum Disorder (ASD) is a complex neurological condition that affects communication, social interaction, and behavior. The prevalence of ASD has increased significantly, now affecting 1 in 36 children in the United States and approximately 2 million people in Brazil. Among the challenges faced by children with ASD is maintaining oral hygiene, as characteristics such as hypersensitivity and hyposensitivity to sensory stimuli make brushing and flossing difficult. The main objective of this study is to analyze the barriers to implementing and maintaining oral care for children with ASD and to identify effective strategies to overcome these challenges. The methodology used was an exploratory literature review, consulting scientific articles, dissertations, and health portals, covering publications from the past 20 years. The SciELO and PubMed databases were used to locate studies related to the themes “Autism,” “Oral Hygiene,” and “Dentistry.” The results indicate that communication difficulties and resistance to changes in routine negatively impact oral hygiene. Visual methods, such as the use of pictograms, and behavioral approaches, such as positive reinforcement and desensitization, have proven effective in establishing hygiene routines. Active parental involvement and the adaptation of dental care to meet children's sensory needs are essential for successful treatment. It is concluded that personalized strategies and interdisciplinary collaboration are fundamental to promoting oral health and improving the quality of life of children with ASD.